Flexible Dual-Frequency Applicator for Local Hyperthermia - Houda Halheit; André Vander Vorst; Smail Tedjini; Rachida Touhami (International Journal of Antennas and Propagation)
A flexible and dual-frequency microstrip applicator for microwave local hyperthermia is described. It is designed on conformal liquid crystal polymer (LCP) substrate and operating at ISM (Industrial, Scientific and Medical) frequencies of 915 MHz and 2.45 GHz. To conform the body’s curvature, the applicator is bent on a cylindrical body. 3D electromagnetic CST Microwave Studio was used to determine the performance of the applicator and to evaluate the specific absorption rate (SAR) distribution in cylindrical human body phantom. The results obtained show that the antenna can be used in curved situation for uniform and superficial treatment.